An Application of Semi-Fowler Positioning to Overcome Nursing Problems Ineffective Breath Patterns in Clients with Chronic Kidney Disease: a Case Study - Sari, Dina Setia Indah; Nistiandani, Ana; Siswoyo; Umayanah (Al-Hijrah Indonesia, 2023)
Chronic Kidney Disease (CKD) or chronic kidney failure is a disease due to decreased kidney function that causes the body to fail to maintain fluid and electrolyte balance metabolism, resulting in urea retention and other nitrogen waste accumulation in the body. This research aims to analyze given this position to lower oxygen consumption and increase maximum lung expansion, the ineffectiveness of the client's breath pattern is more optimal in CKD patients in the Adenium Room of DR. Soebandi Jember Hospital. This type of research is descriptive using the case study approach method. The subject in this case study was one patient affected by CKD with the ineffectiveness of breath patterns. Semifowler position intervention is performed where the position of the head and body is raised by 45°. Result: The application of a semi-fowler position (45° sitting position) for 3x24 hours according to the standard of procedure helps reduce shortness of breath and helps optimize RR in the client so that the problem of ineffectiveness of breath patterns can be resolved. Interventions in regulating the angle of sleep position can meaningfully produce good respiration, so it can be considered one of the interventions to optimize the ineffectiveness of breath patterns.